Essential neuromuscular advice for pathologists (first of two parts) - Ana Cotta; Elmano Carvalho; Antonio Lopes da-Cunha-Júnior; Julio Salgado Antunes; Francineide Sadala de Souza; Heveline Becker de Moura; Andreia Portilho de Brito Pinto; Jaquelin Valicek; Monica Machado Navarro; Frederico Godinho; Eni Braga da Silveira; Maria Isabel Lima; et al. (Surgical and Experimental Pathology)
Abstract Background Neuromuscular disorders are characterized by disturbances in any part of the neurologic pathways, including: the Central Nervous System, the motor neuron of the anterior horn of the spinal cord; the peripheral nerve, the neuromuscular junction, and the muscle. Neuromuscular disorders are considered rare affections but when the prevalences of all subtypes are analysed together they may be encountered by general neurologists and pathologists. Therefore, basic knowledge in this field is necessary to timely guide serologic, molecular, or muscle biopsy investigation for appropriate treatment and/or genetic counselling. Main body The aims of this review are: (1) to briefly describe the prevalence of common neuromuscular disorders; (2) to present basic concepts of topographic neuromuscular diagnosis; (3) to provide essential information for pathologists about the diagnostic approach of common neuromuscular disorders; (4) to present basic concepts of muscle imaging for myopathologists; (5) to provide muscle imaging, and biopsy examples of common neuromuscular disorders. Conclusion A multiprofessional integrated approach is essential for precise neuromuscular diagnosis. Detailed clinical examination with the formulation of phenotypic hypothesis is the basis for appropriate diagnosis in the Surgical-Molecular Pathology era. Clinical, epidemiological, neurophysiological, laboratorial, imaging, molecular, and physiopathologic aspects are essential for adequate neuromuscular diagnosis.